Implementation of Government Collaboration Policy and Citizen Toward Coronavirus: A Literature Review - Sukmawati Sukmawati; Rijal Rijal; Musdalifah Haz (Universitas Negeri Makassar, 2021)
Coronavirus is stated to have almost spread throughout the world. Indonesia became one of the countries exposed to the coronavirus. Therefore, Indonesia has made policies in dealing with coronavirus. One of these policies is the collaboration between the government and Palopo citizens in dealing with the coronavirus. This study aims to determine the implementation collaboration policy between the government and Palopo citizens in dealing with the coronavirus. This study employed literature research. Literature research is research used in collecting information and data with the help of various materials in the library such as documents, books, magazines, historical stories, and news. The sources in this study are based on the object studied and based on sources affiliated with the research. In this study, data collection was obtained from news and articles in online journals. This study showed that the implementation of collaboration policy between the government and Palopo citizens measured the communication, resources, disposition, and bureaucratic structure. These are considered a lack of implementation.